HISTORICAL-PHILOSOPHICAL PRINCIPLES OF THE CONCEPT OF SOVEREIGNTY IN THE FORMATION OF INTERNATIONAL LAW - Leshchenko, Maksym (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2026)
Background. The article is devoted to the historical and philosophical reconstruction of the concept of sovereignty as a fundamental principle of international law. Particular attention is focused on the genesis of this concept in early modern political philosophy and its further transformation in the context of the formation of the interstate legal order. Methods. The methodological basis of the study is the historical-philosophical approach, the method of conceptual reconstruction, and the comparative analysis of political and legal doctrines. At the same time, the principle of contextualization of ideas within the intellectual history of early modernity is applied. Results. It is shown that in the works of J. Bodin, the concept of sovereignty acquires a classical definition as the absolute, indivisible, permanent power of the state. In the political philosophy of T. Hobbes, this idea is transformed into the theory of an unlimited sovereign as a guarantor of security and order, while J. Locke offers an alternative model of limited sovereignty, subordinated to the natural rights of the individual. In the works of G. Grotius, the idea of sovereignty is synthesized with the doctrine of natural law, which lays the foundations of international law as a normative system of interaction between states. It is substantiated that the Westphalian model of international relations institutionalizes the principle of sovereign equality of states and non-interference in internal affairs. Conclusions. It is established that the concept of sovereignty is formed as a result of the interaction of various intellectual traditions, absolutist, contractual and natural law. Its modern understanding is a consequence of historical evolution from the idea of unlimited power to the principle of legally regulated interaction between states. In modern conditions of globalization, sovereignty undergoes a conceptual transformation, which opens up prospects for its rethinking as a dynamic and multi-level phenomenon.